Robust versus Flexible Open Pit Mine Design - Topal, Erkan; Groeneveld, Ben; Leenders, Robert (Australasian Institute of Mining and Metallurgy, 2010)
Strategic planning in mining is an important value accretive process. One of the most important aspects during the planning phase is determining the correct mine and plant design. The traditional mine site design (mine, plant, stockpiles, dumps) develops a fixed system for one set of conditions or expected values. A robust design is a fixed system that is designed to deal with a large range of conditions without changing the system design. A flexible design changes the system dynamically in response to changes in uncertainties. It is hypothesised that a robust design generates less value than a flexible design as it fails to realise the value of actively managing the operation. One of the most critical aspects in creating strategic value from a project is embedded in the design of the system. A flexible design has components that allow the design of the system to change over time. An operational plan is proposed as a hybrid of a robust and flexible design. This paper seeks to compare these different design methodologies. An analysis of the same case study is undertaken to compare these approaches, showing an a traditional net present value (NPV) of $1678 M, robust design NPV of $1787 M and an operational plan NPV of $1867 M – an increase of $170 M.